Análise das comparações e correlações entre problemas de comportamento, práticas parentais e habilidades sociais - Rovaris, Jéssica Aline [UNESP] (2015)
Considering the relevance of evaluating educational practices as well as their relationship with infant behaviors, this paper aimed to describe, compare and correlate maternal educational practices the behavior of children classified by problems of behaviors, education and gender. This research involved 155 mothers of children enrolled in públic schools. These children were in Kindergarten and elementary schools, they had both genders (boys and girls). The following instruments were answered: CBCL, RE-HSE-P e QRSH-P (version for parents). Were conducted Chi-square tests and Student's t-test to comparison analysis, Pearson correlations test and linear regression. Results demonstrated that, for kindergarten and elementary school children, the repertory of social skills constitutes protective factor and the negative practices constitute risk factor for behavioral problems. The girls, especially in elementary school grades, were identified as more skilled and more frequently exposed to positive maternal practices. On the other hand, boys in kindergarten period received the biggest number of behavioral problems and exposure to negative educational maternal practices, indicating the importance of considering the child's gender in the evaluation of the behaviors emitted in the mother-children relationship. This study also found that mothers of children with and without diagnosis of behavioral problems present social skills in the interaction with their children. What seems to distinghish each group is the frequency of the application of negatives and positive practices. Kindergarten children's mothers exhibit skilled even facing their children's behavioral problems, unlike the behaviors emitted in the interaction with elementary school children, in which the usage of negative practices was more frequent. Other important aspect is the confirmation that mothers of clinical group children exhibit more difficulties to identify and reinforce...